Interactional Features of L2 Pragmatic Interaction in Role‐Play Speaking Assessment. Issue 1 (16th October 2019) - Youn, Soo Jung
Abstract : This study explicates the nature of second language (L2) pragmatic interaction focusing on the quantitative function of interactional features. A relationship between the fine‐grained interactional features elicited from learners' role‐play performances at varying levels and trained raters' scores was investigated. The corpus of 102 learners' role‐play performances was transcribed turn by turn and analyzed qualitatively to identify recurrent interactional phenomena, which formed the basis of data‐driven coding schemes that are grounded in conversation analysis. Three levels of interactional features —length of interaction, engaging with interaction, and sequential organizations —were coded. The coded data were extracted using the CLAN program and analyzed quantitatively to examine what interactional features distinguished among varying performance levels. The linear regression analysis indicated that the combination of nine significant interactional features accounted for 74.7% of the variance in the raters' scores. The discriminant function analysis revealed that the interactional features elicited from the role‐plays that involve formal pragmatic functions were important variables in distinguishing among the performance levels. This study confirms that the interactional features deserve a prominent place in defining L2 pragmatic interaction. The author discusses practical implications for teaching and assessing interactive pragmatic performance, as well as methodological issues underlying quantifying spoken interaction. Abstract :